Poetry Musicalization as Desire Manifestation of Ari-Reda Group in Sapardi Djoko Damono’s Poems - Arie Azhari Nasution; Ricky Yudhistira Nasution; Evi Marlina Harahap (Journal Polingua: Scientific Journal of Linguistics, Literature and Language Education, 2020)
Viewed in the past 10 years, poetry musicalization had become a trend in Indonesia. Many groups change a written poem into musical. Not only creating musical poetry, this group also utilizes technological developments to publish it. The publication is done by uploading poetry musicalisation to social media so that it can be listened by public. One of the groups best known for the music he created is the Ari-Reda group, which from the beginning focused on the poems of Sapardi Djoko Damono. Of course, many things can be highlighted when looking at the process of reproduction of a work. One of them expressed a desire as an effort to fulfill themselves. Ari-Reda in this case, expressed desire through the poem "Aku Ingint" by Sapardi Djoko Damono.  The results show that Ari-Reda's desire to the poemss as a fulfillment of desires between humans and humans and humans with love that is never finished because it never having time to say the desire.